2020
DOI: 10.1101/2020.12.02.408070
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lactate receptor HCAR1 regulates neurogenesis and microglia activation after neonatal hypoxia-ischemia

Abstract: Neonatal cerebral hypoxia-ischemia (HI) is the leading cause of death and disability in newborns with the only current treatment option being hypothermia. An increased understanding of the pathways that facilitate tissue repair after HI can aid the development of better treatments. Here we have studied the role of lactate receptor HCAR1 (Hydroxycarboxylic acid receptor 1) in tissue repair after HI in mice. We show that HCAR1 knockout (KO) mice have reduced tissue regeneration compared with wildtype (WT) mice. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Lauritz et al. demonstrated, using the neurosphere assay, that brain cells lacking HCAR1 had reduced proliferation and repair abilities ( 51 ). Moreover, MCT1 is mainly used by oxidative cells for extracellular lactate intake, and MCT4 is mainly used to release accumulated lactate into the extracellular milieu, in many cases by hypoxic and/or highly glycolytic cells ( 52 – 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lauritz et al. demonstrated, using the neurosphere assay, that brain cells lacking HCAR1 had reduced proliferation and repair abilities ( 51 ). Moreover, MCT1 is mainly used by oxidative cells for extracellular lactate intake, and MCT4 is mainly used to release accumulated lactate into the extracellular milieu, in many cases by hypoxic and/or highly glycolytic cells ( 52 – 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors showed that stimulation of HCAR1 leads to the activation of cell survival signalling promoting cell proliferation via the inhibition of apoptosis and stimulates the secretion of several angiogenic factors in a PI3K/Akt-CREB signalling pathway-dependent manner [44]. Interestingly, an essential part of the repair process after a neonatal brain injury is the generation of new cells by increase of proliferation and differentiation of stem cells, Lauritz H. K. et al, by neurosphere assays, demonstrated that the cells lacking HCAR1 had reduced proliferation ability [45].…”
Section: Discussionmentioning
confidence: 99%
“…The hypoxic-ischemic injury activated microglia can also impact NPC proliferation through direct cell-cell interactions (169). A recent study used single-cell sequencing to construct myeloid cell composition map of the periinfarction area after ischemic stroke in rats, and further distinguished microglia state conducive to neural regeneration, the underlying mechanism of which can be attributed to SOX2 and its involvement in the regulation of Akt and CREB signaling pathways (170).Studies have shown that the knockout of the HCAR1 gene inhibits the activation of microglia, thereby weakening neurogenesis after hypoxic-ischemic brain injury (171). In vitro experiments showed that NSC cultured in a conditional medium with anti-inflammatory microglia subtypes exhibited better cell survival, stronger migration ability, and lower astrocyte differentiation ability (172).…”
Section: Neurogenesismentioning
confidence: 99%